Pengaruh Molaritas dalam Teknik Spray terhadap Performa Fotodetektor Berbasis ZnO - Okky Fajar Tri Maryana; Anisa Fitri; Mohamad Samsul Anrokhi; Wahyu Solafide Sipatuhar; Eka Nurfani (Jurnal Teori dan Aplikasi Fisika, 2021)
ZnO:Fe thin films has been successfully carried out by a simple spray pyrolysis method. The thin film was grown on ITO (Indium Tin Oxide) substrate with a metal-semiconductor-metal (MSM) structure. ZnO:Fe thin film characters as photodetector application include morphological structure, and electrical properties. SEM image results show the molarity difference can affect the particle size. The Current-Voltage (I-V) characterization shows that different solvent effects and molarity give different sensitivity. Sample ZnO:Fe 0.5M Ethanol has the highest sensitivity compared to other samples because it has a fairly low current and high bright current.